Mathematical modelling of droplets climbing an oscillating plane - Bradshaw, Joel (2016)
Recent experiments [P. Brunet, J. Eggers, and R. Deegan, Phys. Rev. Lett. 99, 114501 (2007)] have shown that a liquid droplet on an inclined plane can be made to move uphill by sufficiently strong, vertical oscillations. In order to investigate this counterintuitive phenomenon we will derive three different models that qualitatively reproduce the main features of the experiment.